The Summer School Oncology Groningen: Improving a Successful International Course by Refining the Old, Maintaining What’s Good - E. C. E. Boske; P. H. Nienhuis; C. Hammer; M. Jalving; F. A. E. Kruyt; J. de Vries; J. L. N. Roodenburg; M. J. H. Metman; S. Kruijff (Journal of Cancer Education, 2022)
For more than two decades, the International Summer School Oncology for Medical Students (ISOMS) has organized a biennial 2-week international summer school program in Groningen, the Netherlands. The summer school aims to increase knowledge about general cancer care, reduce fear of talking to cancer patients, and expose students to cancer-related problems. After 22 years, there was a need to improve the summer school format, the application procedure, and the intensity of the course. Here, we describe and evaluate these and additional changes that were made to the program. Several changes were made to the summer school format. The course was shortened from 10 days to a more intensive 7 days. The scientific program was integrated with the clinical program and students were taught scientific writing and presentation skills. The application process involved a personal video pitch. Importantly, the new summer school format was organized by a committee in which medical students had the lead. To evaluate the changes to the summer school, we conducted knowledge tests and regularly obtained feedback. There was a high overall student satisfaction, with a median score of a 9 out of 10. Students appreciated the interactive sessions and practicals and the scientific program, and were satisfied with the course level. All students had improved test scores. Improvement points highlighted the need for a less packed schedule and more lectures on basic oncology principles, or were related to specific lectures. The student-led innovation and adaptation of the ISOMS has been successful.